INVOLVEMENT OF RESPONSIBLE EMPLOYEES IN THE FUNDAMENTAL REFORM OF THE FACTORS THAT LEAD TO CORRUPT SITUATIONS IN ORGANIZATIONS AND THEIR ELIMINATION - Nigora Rasulmatova Khusanovna (American Journals Publishing, 2024)
Corruption within organizations has long been a widespread problem that undermines transparency, ethics, and overall organizational health. This research paper examines the factors that influence corruption and proposes a radical reform approach that emphasizes the participation of responsible officials in its elimination. By empowering and engaging employees, organizations can create a culture of honesty, accountability and ethical behavior, thereby reducing the risks associated with corruption. This article highlights key strategies and initiatives that can be implemented to eliminate corruption and create a sustainable, corruption-free organizational framework and enabling environment.